High quantum yield pure blue emission and fast proton conduction from an indium–metal–organic framework. Issue 32 (25th July 2019) - Zhai, Lu; Yu, Jing-Wei; Zhang, Jin; Zhang, Wen-Wei; Wang, Lifeng; Ren, Xiao-Ming
Abstract : A 3D anionic In 3+ –MOF integrates the multifunctionality of pure blue luminescence with a high quantum yield of 61.4% and water-mediated fast proton conduction with σ = 2.90–9.22 × 10 −3 S cm −1 at 25–60 °C and 99% RH. Abstract : A multifunctional material, with two or more types of functionalities in a single material, might give new phenomena and novel applications. Metal–organic frameworks (MOFs) or porous coordination polymers (PCPs) can be utilized as a highly versatile and tunable platform for exploring multifunctional materials. In this study, an extra thermally stable indium–MOF (1 ) was synthesized via self-assembly of 1, 1′-ethynebenzene-3, 3′, 5, 5′-tetracarboxylic acid (H4 EBTC) with an indium salt under solvothermal conditions. MOF1 crystallizes in a tetragonal space group P 4/ mmm and shows a three-dimensional (3D) anionic framework with one-dimensional (1D) channels along the c -axis direction, and charge-balancing [(CH3 )2 NH2 ] + cations together with lattice DMF and water molecules are accommodated in channels. This multifunctional MOF emits pure blue luminescence under ambient conditions, arising from the π* → π electron transition in EBTC 4−, with CIE coordinates of (0.16, 0.07), and shows the highest quantum yield of 61.4% among indium–MOFs. Alternatively, 1 features fast proton conductivity with σ = 3.49 × 10 −3 S cm −1 at 25 °C and 99% RH, attributed to the efficiently synergistic proton transfer in the H-bond networks constructed by [NH2 (CH3 )2 ] + cations, lattice water molecules in channels and carboxylate groups in the framework. The notable level of performance of1, combined with good hydrolytic and extra thermal stability, offers great opportunities for its future applications, and it may behave as a kind of promising multifunctional MOF material.